Pengaruh Kompetensi Kerja Terhadap Kinerja Karyawan Pada PT. Bank Rakyat Indonesia (Persero) Tbk Unit â€œBâ€ Pekanbaru - Azis, Abdul; Hendriani, Rahayu (Eko dan Bisnis: Riau Economic and Business Review, 2023)
The purpose of this study was to determine the effect of competence on employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk Unit â€œBâ€. To achieve this goal, research was conducted using a sample of 32 people, using the census/saturated sampling method. The data analysis method used simple linear regression. Based on the test results on the competence variable has a significant effect on employee performance at PT. Bank Rakyat Indonesia (Persero) Tbk Unit â€œBâ€, this is proven based on the t-test found that t-count is greater than t-table (8.866 > 2.042). R. Square (R2) is 0.724 (72.4%) this is proven based on the results of the determination test where the R2 value is 0.724. Recommendations that can be submitted are expected that the company can pay attention to employees so that employees in carrying out their work always think today should be better than yesterday because this statement received the lowest response from respondents